UJI AKTIVITAS ANTIOKSIDAN DAN BIOTRANSFORMASI EKSTRAK ETANOL DAN HEKSANA DAUN KELAPA SAWIT UNTUK SUPLEMEN KESEHATAN - Kresnawaty, Irma; Permatasari, Galuh Wening; Widodo, Widodo; Santoso, Djoko (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
Oil palm fronds and leaves are wastes of oil palm plantations which are abundantly available in Indonesia and contain polyphenolic compounds which have high economic potential and health value. However, the potential for polyphenols from oil palm leaf extract (OPLE), which has antioxidant activity, has not been utilized optimally until now. In this research, an antioxidant food supplement from OPLE which is rich in polyphenolic compounds was developed. OPLE was prepared using ethanol as a solvent and concentrated by vacuum evaporation, then separated by liquid-liquid column chromatography and identified by LC-MS. The total phenolic yield of the ethanol extract of palm leaves contained was higher phenolic content than the hexane extract, while the phenolic content and antioxidant content of the oldest leaf were higher than the 17th leaf. Separation of the active antioxidant ingredients was carried out by liquid-liquid column chromatography with chloroform eluent: methanol = 4: 1 v/v which is expected to separate the active compounds. The content of flavonoids contained in this fraction is 6-Methoxy-2-[2-(3'-methoxyphenyl) ethyl] chromone. Biotransformation using tannase enzyme produced the increase of flavonoid content and antioxidant of oil palm extracts. Keywords : antioxidant, biotransformation, immunomodulator, OPLE, supplement